Foundational Research in Entrepreneurship Studies Insightful Contributions and Future Pathways (Springer International Publishing, 2018)
This book draws attention to the classics, seminal articles in entrepreneurship that have made profound contributions to the field's emergence, development, and maturity. In each chapter, a classic is identified, ideas contained therein that are still relevant to the field are discussed, and subsequently follow-up research that is being conducted based on these ideas is highlighted, including possible areas of future research. Scholars will embrace this systematic effort to identify and reveal the contribution of classic articles in entrepreneurship research and their impact on subsequent scholarship. .